If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = x + 4 Reorder the terms: -10 + 4x = x + 4 Reorder the terms: -10 + 4x = 4 + x Solving -10 + 4x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + 4x + -1x = 4 + x + -1x Combine like terms: 4x + -1x = 3x -10 + 3x = 4 + x + -1x Combine like terms: x + -1x = 0 -10 + 3x = 4 + 0 -10 + 3x = 4 Add '10' to each side of the equation. -10 + 10 + 3x = 4 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 4 + 10 3x = 4 + 10 Combine like terms: 4 + 10 = 14 3x = 14 Divide each side by '3'. x = 4.666666667 Simplifying x = 4.666666667
| g(x)=1/3f(x) | | 6(v-1)=12 | | 16x+7y=4232 | | (5-u)(5u-4)=0 | | 7(28)+14-6(28)=-4-10 | | u/3-3.2=-10.7 | | 2(b-7)=8 | | 9x^2+7-14=0 | | 3x+x=3 | | 6=2y+y | | 3(4x+4)-4= | | 36=2x+2x | | -(5x-4)+3x-6=-2 | | 6r+4r=70 | | (3x+6)+(2x-1)+90=180 | | 7(d-9)=7 | | -5=5/7n | | w^2(w+7)=18 | | 36x^2+30x-36=6x-4 | | 6x-(3x+6)=15 | | 11p+6=2(p-6) | | 5/7*56 | | 8x-2=5x-68 | | (b+3)(b+5)=0 | | 3ay/2ay | | 40x=323.07 | | w-2=O | | -11y+6x=260 | | 6x-11y=-260 | | 8(6c-1)-8=46c+8 | | 6(a-10)=12 | | 260+6x=11y |